(untitled) (Research, Society and Development, 2022)
Knowledge has become one of the most precious and strategic resources for an organization, and its management is therefore an important tool for organizations to seek to achieve more efficiency and higher quality of services based on a process that supports constant identification, creation, sharing and using their knowledge. In this context, the general objective of this research is to investigate the current scenario of Knowledge Management (KM) at the Rondônia Federal University (UNIR) with regard to knowledge flows related to its administrative activities. It is an exploratory and descriptive research, adopting a qualitative approach, through a case study, with bibliographical research to build the theoretical framework and documentary research to support the analysis of the results. As a collection instrument, an electronic questionnaire sent to all technical staff and professors in administrative activities at the institution was used. The results show that the institution does not have a formalized KM strategy, in addition to a deficient scenario in several essential factors for the creation of an environment conducive to learning and knowledge sharing and little incentive to a knowledge sharing culture. Parallel to this, only three of the twenty KM practices or tools presented to the participants had relative prominence regarding the frequency of use, namely: Electronic Document Management (EDM), collaboration tools and virtual collaborative spaces.